2017
DOI: 10.18517/ijaseit.7.2.1499
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Framework in Oil Field Development Project by Enclosing Fishbone Analysis

Abstract: Fishbone analysis process is a conceptual stage in an engineering role and product design. It's a systematic method to analysis a failure system that was longer used in electronic industry application but not limit to use in oil and gas industry. In risk management concept that a failure as a risk shall prevent and identify in beginning process that may require to minimize them to happen in product and application in oil field equipment. The main interest of this paper is to propose for the potential of fishbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The lack of initiating to identify the risk of the project will affect to project itself. Some barrier and project constraint is becoming a risk at this point that does not recognize at risk for the entire project without a systematical method [26].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of initiating to identify the risk of the project will affect to project itself. Some barrier and project constraint is becoming a risk at this point that does not recognize at risk for the entire project without a systematical method [26].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this study, a Chinese manufacturer can choose the best scheme for its supply chain management with the lowest risk. Hamid et al (2017) prepared a risk management framework in the Oil Field Development Project. This study was conducted using the Fishbone Analysis method for finding possible risk causes.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies (Tummala & Schoenherr, 2011;Li & Chen, 2014;Sun et al, 2015;Hamid et al, 2017) found that supply chain risk management requires a process sequence, a tool for managers to make strategic decisions. Furthermore, any risk events and risk causes must be identified and assessed first.…”
Section: Introductionmentioning
confidence: 99%
“…It is a challenging task for industrial practices [11]. Material and process selection is one of basic requirements in the manufacture of oil and gas equipment since manufacturers are required to control the process of welding and testing as well [12,13].…”
Section: Introductionmentioning
confidence: 99%